Oxford German cartoon-strip vocabulary builder - illustrations by Claire Bretécher; edited by Neil Morris and Roswitha Morris (Oxford University Press, 2000)
While there are other cartoon dictionaries on the market, most of them provide only single cartoons. This attractive series, on the other hand, provides whole strips which tell a story and effectively bring context and other memorable features to one's learning. And only this series offers cartoons done in full color, and written by a popular cartoonist. These vocabulary-builders are the perfect starting place for people who want to begin, or else strengthen, their acquisition of French, German, or Spanish